Synthesis and olfactory evaluation of allylic α‐quaternary ether ketones. (16th December 2018) - Lempenauer, Luisa; Soupart, Aline; Lemière, Gilles; Duñach, Elisabet
Abstract: Unprecedented α‐oxygenated β, γ‐unsaturated ketones bearing a quaternary carbon at the α‐position were synthesized in two steps from readily available α, β‐unsaturated ketones. The compounds were prepared on a gram scale under mild conditions via a key rearrangement step catalysed by 1 mol% of p ‐toluenesulfonic acid as a low‐priced and sustainable catalyst. The olfactory properties of this novel family of odorants as well as of some derivatives have been assessed, revealing a quite broad odour spectrum and a pronounced susceptibility of the olfactory properties towards structural changes. Abstract : Olfactory properties of a series of new compounds issued from an acid‐catalysed rearrangement of 2‐oxa diallylic alcohols.